If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-24(2x+1)+16x=112+16+44
We move all terms to the left:
-24(2x+1)+16x-(112+16+44)=0
We add all the numbers together, and all the variables
-24(2x+1)+16x-172=0
We add all the numbers together, and all the variables
16x-24(2x+1)-172=0
We multiply parentheses
16x-48x-24-172=0
We add all the numbers together, and all the variables
-32x-196=0
We move all terms containing x to the left, all other terms to the right
-32x=196
x=196/-32
x=-6+1/8
| 7(x-2)=5-9x | | 2x+3(x+1)=5(x+3) | | 30+25x=256 | | 2.18x+49=4.7524+7x | | t/12+20=18 | | 2-3x=-4x+7 | | 9x+10+6+2=54 | | 180=8x-6 | | 7x+10=5x | | -1/2p=32 | | 3+9p=7p−11 | | 9.5=3x+4/2 | | 5x-4=x-(4-x) | | v/6+3=-12 | | -7(5k-1)=7-2k | | 64=7h+43 | | 7a+-4=8+a | | 25+30x=256 | | 6(-y-5)+6=-9y | | 10x^2+8x=1 | | -5-x=-2(x+8) | | -105=-5(5x-4) | | |7x+9|-12=3x-23 | | 6(2-c)=54 | | a^2+4a+0=0 | | 90+k/3=120 | | 7x+9|-12=3x-23 | | 6(2c)=54 | | 23x-42x-80-9=63 | | -16-6n=-3(4n-2) | | -3+r=7 | | (x+3)+(9x-43)=180 |